Stress Levels, Emotional Eating, Snacking Habits, and Nutrient Intake among College Students during the COVID-19 Pandemic - Afia, Difa; Dwiriani, Cesilia Meti; Dina, Resa Ana (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study analyzed the correlation between stress levels and emotional eating, snacking habits, and nutrient intake among college students. This cross-sectional study involved 98 students as subjects who were selected by convenience sampling through an online questionnaire. The result showed 70.4% of the subjects experienced moderate stress, 52% were emotional eaters, 64.3% consumed snacks more than 3 times a day, 39.7% had a protein deficit, 36.7% had an excessive fat intake, and 49% had an energy and carbohydrate intake classified as severely deficit. This study found a positive correlation (p=0.04; r=0.21) between stress levels and emotional eating. Among college students, a high prevalence of moderate stress level was associated with emotional eating.